ANOMALOUS EARLY 20TH CENTURY SEDIMENTATION IN PROGLACIAL GREEN LAKE, BRITISH COLUMBIA, CANADA - Menounos B. (My University, 2006)
Annually laminated sediments were recovered from Green Lake, a proglacial lake in the southern Coast Mountains in British Columbia, to examine their potential as a temperature proxy. Varve thickness is moderately correlated with temperature anomalies (A.D. 1900-1994) and annual maximum mean daily discharge of Lillooet River (A.D. 1930-1999), but these relations are not stable through time. Following A.D. 1977, the relation between varve thickness and annual maximum mean daily discharge is stronger. Prior to A.D. 1977, varve thickness is correlated with March to October air temperature, which controls the intensity and duration of glacier runoff. Varve thickness is weakly correlated with reconstructed air temperature records for North America and the Northern Hemisphere for the period A.D. 1600-1976. Less extensive glacier cover may explain the lack of a clear temperature signal in the varved sediment record prior to A.D. 1600 and following A.D. 1977. The period of highest lake sedimentation, from A.D. 1920 to 1945, coincides with rapid retreat of glaciers in the watershed. The lack of a similar level of sedimentation in the varve chronology suggests that glacier recession during the period 1920-1945 was higher than at any time in the past 600 years. © 2006 NRC Canada.